Синонимические повторы в русской речи (на материале художественной литературы XIX–XX вв.) - Синочкина, Б. М. (Kalbotyra, 1981)
Synonymic collocations in Old Russian were used as the necessary means in defining and strengthening semantic meanings of words. Owing to the development and perfection of the language and its lexico-semantic system, the usage of these synonymic collocations became inexpedient.As a relic, synonymic collocations are preserved in speech which is more expressive and not so precise. Nowadays synonymic repetitions are found in fiction thanks to the fact that fiction reflects all the phenomena of any spoken language.